PENGEMBANGAN MODEL PEMBELAJARAN IPS TERPADU BERBASIS LINGKUNGAN SEKITAR - Iin Purnamasari (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2011)
SARI?é?áIt must be recognized that the subjects belonging to the education of Social Sciences (IPS) in Indonesia have not recognice from the public. There are some indications to justify this statement. First, the national exam originally did not include exams that must be tested. Second, parents are more proud if his son has high score in mathematic, despite he has low score of sosial studies.. Third, social study learning did less seriously or carelessly. Less respect for social studies in schools is determined by several factors. First, the myth that believe only those who pursue science lesson was the one who will be successful in life. Although in fact they are not. Second, the sosial studies material that is too big has less relevance to the real world of students. Third, unprofessional social studies teacher also determines the student disinterest. ?é?áApart from that problem, social studies education has a strategic significance to increase student?óÔé¼Ôäós personality so that they can become a good members of the public. It must be received that social studies is needed to give the students a balance of thinking, so that the right brain and left brain can function optimally so that it can succeed in the midst of modern society that has full of change. The question is whether today's social studies education has been able to those function? If it?óÔé¼Ôäós not, so how the strategy to restore the function of learning social studies in order to have benefits for students, especially elementary school and the community? Keywords: sosial sudies Integrated Learning, Environment